MASJID GHAUDIYAH DAN PENDIDIKAN ISLAM: INTERNALISASI NILAINILAI ISLAM BAGI ETNIS INDIA MUSLIM DI KOTA MEDAN - Dinda Saqina Ningrum; Zaini Dahlan (Kuttab : Jurnal Ilmu Pendidikan Islam, 2022)
Apart from being a means of worship, the Muslim mosque is also an educational centre. This article will discuss the Ghaudiyah mosque, which is used as an educational medium for internalising Islamic values for Muslim Indians in the city of Medan. Through a qualitative method with a historical approach, the research found that the first Ghaudiyah Mosque is the second mosque shaded by the India Seasons Foundation, Medan city. Second, Islamic education activities under the auspices of the Muslim India Foundation areÂ  systematic studies, tahfiz houses, and guidance for converts to Islam, including creed, worship, and morals. A good funding factor makes mosque activities run well, although there are still some converts who do not take regular educational studies.